Inside BAR (The Biblical archaeology review, 1983)
Who were the people of the Exodus? Have archaeologists uncovered any buildings, artifacts, pottery or other evidence of a people who traveled north from Egypt and migrated into Canaan? Scores of surveys and excavations were conducted in the Sinai from the summer of 1967 until Israel turned the Sinai over to Egypt in 1982. […]